PERBANDINGAN PENANGANAN PENGADILAN AD HOC INTERNASIONAL DALAM PERSPEKTIF HUKUM INTERNASIONAL(Studi Perbandingan International Criminal Tribunal for the Former Yugoslavia dengan International Criminal for Rwanda) - Alif Daffa Raditya (2023)
Human Rights, highly regarded by the international community, seem to hold a sacred status and occupy the highest position compared to other international norms and customs. The Rome Statute of 1998, the Geneva Conventions of 1949, and International Humanitarian Law, however, cannot guarantee the international community's protection from various forms of discrimination and violations of individual rights. Discrimination leading to aggression resulting in millions of casualties remains a major obstacle to achieving world peace. The massacres that occurred in Yugoslavia and Rwanda are examples of Crimes Against Humanity and War Crimes, originating from ethnic discrimination and social envy. The genocidal crimes that took place in the former Yugoslavia and Rwanda have left a dark stain on the international community. Serious violations of the Geneva Conventions of 1949 and International Humanitarian Law prompted the international community to respond by establishing temporary international tribunals specifically designed to prosecute the perpetrators of these crimes. The International Criminal Tribunal for the former Yugoslavia and the International Criminal Tribunal for Rwanda are international tribunals created with the objective of delivering justice and preserving peace in the regions that were at the center of these major conflicts.